Strategi Pembelajaran Pendidikan Agama Islam di MA Al Ittihadiyah: Integrasi Bahasa Arab sebagai Media Penguatan Nilai Islami - Nasution, M. Irfan Hakim; Pasaribu, Munawir (EL-EMIR Institute, 2025)
This study analyzes the learning strategies of Islamic Religious Education (PAI) at MA Al Ittihadiyah with a focus on integrating Arabic as a medium for strengthening Islamic values. PAI plays a strategic role in shaping religious character, while Arabic is essential as the language of the Qur’an and Hadith. A qualitative descriptive approach was employed using observation, interviews, and documentation, with data analyzed through Miles and Huberman’s interactive model. The findings show that PAI strategies were implemented through interactive lectures, group discussions, memorization, recitation, and daily worship habituation. The integration of Arabic not only enhanced students’ language competence but also reinforced the internalization of Islamic values. Supporting factors included teacher competence, the school’s religious culture, and parental support, while obstacles were differences in Arabic proficiency, limited digital media, and tight schedules. The study concludes that PAI strategies based on Arabic integration are relevant, effective, and serve as a model for adaptive Islamic education in the modern era.